Bacteria and virus evolution: a model for the study of natural selection - Turner, Paul (Henry Stewart Talks, 2007)
Experimental evolution, Classic experiments using bacteria and viruses, Evolution of antibiotic resistance in bacteria, Evolution of higher and lower virulence in pathogens, Evolution of pathogen emergence
Updated at 2020/09/18